2008
DOI: 10.1080/15283480801938440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Family Functioning and Identity Confusion on Substance Use and Sexual Behavior in Hispanic Immigrant Early Adolescents

Abstract: The present study examined the relationships of (a) changes in adolescent-reported family functioning and (b) changes in identity confusion to onset of substance use and sexual behavior in a sample of 250 Hispanic adolescents from immigrant families. Adolescents were followed for 3 years. Results indicated that adolescents whose identity confusion scores increased over time were most likely to initiate cigarette use, alcohol use, and sexual behavior during the course of the study. Adolescents whose identity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 34 publications
8
46
0
1
Order By: Relevance
“…While the potential utility of identity issues in treatment for PTS is speculative at this point, interventions that focus on identity issues have produced some promising initial research in terms of potentially helping individuals with other identity-related psychological difficulties (e.g., Archer 2008;Berman et al 2008;Ferrer-Wreder et al 2008;Kerpelman et al 2008;Kurtines et al 2008;Lerner and Galambos 1998;Montgomery et al 2008;Schwartz et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…While the potential utility of identity issues in treatment for PTS is speculative at this point, interventions that focus on identity issues have produced some promising initial research in terms of potentially helping individuals with other identity-related psychological difficulties (e.g., Archer 2008;Berman et al 2008;Ferrer-Wreder et al 2008;Kerpelman et al 2008;Kurtines et al 2008;Lerner and Galambos 1998;Montgomery et al 2008;Schwartz et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is conceivable that difficulties in negotiating the demands from the two cultures can lead to lack of identity coherence and increased identity confusion and distress (Syed et al 2013). Indeed, identity confusion has been strongly associated with emotional distress (i.e., depressive symptoms) and with an increased likelihood of initiating alcohol use in early to mid-adolescence among Hispanic immigrant youth (Donovan et al 2012;Schwartz et al 2008).…”
Section: Identity Development and Immigrationmentioning
confidence: 95%
“…Latinas who receive tangible and emotional support, and have strong attachments to their families, cope better with stress and report less alcohol and illicit drug use compared to Latinas without support—lowering their risk of engaging in risky sexual behavior [4,7,23,24,25,26]. After controlling for age, sex, and homelessness among Puerto Rican women, Mino et al (2006) found that emotional support was negatively associated with drug injection frequency (standardized coefficient = −0.168, p = 0.02), reducing the risk of injection-related HIV infection [27].…”
Section: Introductionmentioning
confidence: 99%